Stars Fell on Alabama - Carmer, Carl, 1893-1976 (Book collections on Project MUSE., 2000)
Stars Fell on Alabama is truly a classic. The book enjoyed enormous popularity and notoriety when it was first published (it was a selection of The Literary Guild and also sold widely in Europe). It can be described as a book of folkways-not journalism, or history, or a novel. At times it is impressionistic; at other times it conveys deep insights into the character of Alabama. Carmer visited every region of the state, always accompanied by someone intimately familiar with the locality. The mosaic that emerges from the pages of his book portrays Alabama's human landscape in all its variety, an.